Implementasi Sistem Pengukuran Tinggi Badan Manusia Menggunakan Arduino Uno untuk Peningkatan Layanan Kesehatan (Studi Kasus Desa Kalilangkap, Kecamatan Bumiayu, Kabupaten Brebes) - Diva Karunia Ramadhani; Syafira Khoerunisa; Husni Senja Wisanggani; Maleekha Ollyvia Rifki; Annisa Zharifa Nurfauzi; Silviana Febri Nur Azmi; Hanan Aldi Rizqullah; Shelsa Suci Cahyani; Aulia Nesya Ardita; Alya Salzabila; Alif Azis; Muhammad Azka Dhiyaa Ramadlan; Meydy Fauziridwan; Ambar Pujiyatno (Universitas Respati Indonesia, 2026)
Height measurement is an important parameter for monitoring growth and assessing nutritional status. However, in village health services, height measurement is still commonly conducted manually, which may lead to measurement errors and inefficiency. This activity aims to apply an Arduino Uno–based height measurement system as an alternative to manual measurement methods in Kalilangkap Village, Bumiayu District, Brebes Regency. The method used was descriptive with an observational approach supported by a literature review to examine the characteristics, advantages, and limitations of the Arduino Uno–based system. The system consists of an Arduino Uno microcontroller, an HC-SR04 ultrasonic sensor, and an LCD to display measurement results. The results show that the system is able to display height measurement results automatically and is more practical than manual methods. The discussion indicates that Arduino Uno offers advantages in terms of ease of use, sensor integration, and operational stability. However, measurement accuracy is still influenced by sensor calibration, body position during measurement, and environmental conditions. Overall, the Arduino Uno–based height measurement system has the potential to support more efficient and consistent height measurement in village health services when used with proper procedures